School-aged Children with Mild Bilateral and Unilateral Hearing Loss: Parents' Reflections on Services, Experiences, and Outcomes. (31st October 2017) - Grandpierre, Viviane; Fitzpatrick, Elizabeth M; Na, Eunjung; Mendonca, Oreen
Abstract: Following the establishment of newborn hearing screening programs, age of identification and length of time before receiving interventions has been reduced for children, including those with milder degrees of hearing loss who were previously not identified until school age. This population of early-identified children requires new support programs for parents. Although literature is emerging on how parents experience the initial years, there is limited information on support needs during early school years. The objectives were to gain insights into parents' experiences with services during the early period of identification until early school years, as well as their perceptions of the consequences of hearing loss on their child's overall development. A qualitative research design informed by Interpretive Description was employed. Individual semi-structured interviews were conducted with 12 parents of children identified with mild hearing loss. Transcripts were analyzed using a constant comparative method. Four themes emerged from the data: early experiences with services and hearing technology, effects of hearing loss on social functioning, effects of hearing loss on language and academics, and experiences in early school years. From parents' perspectives, more support during the early school years is needed to help ensure academic success.